2013
DOI: 10.1038/srep02013
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Temperature of the mid-Piacenzian Ocean: A Data-Model Comparison

Abstract: The mid-Piacenzian climate represents the most geologically recent interval of long-term average warmth relative to the last million years, and shares similarities with the climate projected for the end of the 21st century. As such, it represents a natural experiment from which we can gain insight into potential climate change impacts, enabling more informed policy decisions for mitigation and adaptation. Here, we present the first systematic comparison of Pliocene sea surface temperature (SST) between an ense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
234
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 153 publications
(242 citation statements)
references
References 70 publications
7
234
1
Order By: Relevance
“…Numerous independent proxy data for the Pliocene (Haywood et al, 2016a) suggested predominant warming over the North Atlantic and the Arctic region and wetter climate over land (Salzmann et al, 2008). The climate simulations under the PlioMIP1 tended to underestimate the warming over the Northern Hemisphere middle and high latitudes Dowsett et al, 2012Dowsett et al, , 2013 although the latitudinal warming gradient was reproduced qualitatively. Hill et al (2014) pointed out a robust contribution of surface albedo due to changes in vegetation and ice sheets and ice-albedo feedbacks (sea ice and snow) to the warming amplifications over the polar regions.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous independent proxy data for the Pliocene (Haywood et al, 2016a) suggested predominant warming over the North Atlantic and the Arctic region and wetter climate over land (Salzmann et al, 2008). The climate simulations under the PlioMIP1 tended to underestimate the warming over the Northern Hemisphere middle and high latitudes Dowsett et al, 2012Dowsett et al, , 2013 although the latitudinal warming gradient was reproduced qualitatively. Hill et al (2014) pointed out a robust contribution of surface albedo due to changes in vegetation and ice sheets and ice-albedo feedbacks (sea ice and snow) to the warming amplifications over the polar regions.…”
Section: Introductionmentioning
confidence: 93%
“…Note that the PRISM4 SST reconstruction is not updated (Dowsett et al, 2016) since PRISM3D. The SST reconstruction is characterized as extremely high SST in the North Atlantic high latitude, low-to-mid-latitude warming gradient (limited change in the tropics and warming in the middle latitude, respectively), and remarkable warming in mid-latitude coastal areas (off the west coast of North America and South America, and off the east coast of the Eurasian Continent; Dowsett et al, 2009Dowsett et al, , 2013.…”
Section: Data-model Comparison Of Sstmentioning
confidence: 99%
“…The ocean component MPI-OM (Marsland et al, 2003), including the dynamics of sea ice formulated using viscous-plastic rheology (Hibler, 1979), has an average horizontal resolution of 3 Â 1.8 with 40 uneven vertical layers. The climate model was previously utilized to analyse the climate of the last millennium (Jungclaus et al, 2010), the last glacial (Zhang et al, , 2014 and the last interglacial period (Varma et al, 2012;, as well as warm climates of the Miocene (Knorr et al, 2011;Knorr and Lohmann, 2014) and the Pliocene (Stepanek and Lohmann, 2012;Dowsett et al, 2013). To evaluate the corresponding changes in SIC, two sensitivity experiments with high and low solar radiation anomalies (1367 ± 3 W/m 2 ) were performed under pre-industrial (PI) conditions.…”
Section: Model Description and Experimental Designmentioning
confidence: 99%
“…Sea surface temperatures (SSTs) were up to 8 • C warmer than at present in the Nordic Seas as opposed to only ∼ 2-4 • C in the midlatitudes . The amplified warming has been suggested to be related to an enhanced Atlantic Meridional Overturning Circulation (AMOC) (see, e.g., Dowsett et al, 2013;Robinson, 2009). However, model simulations indicate a similarto-present AMOC during the mPWP, supporting the notion that the amplified warming in the Nordic Seas was a result of increased radiative forcing .…”
Section: Introductionmentioning
confidence: 99%